Comparison of the last five world championships in men's handball - Skoufas, D. (Gymnasium - Scientific Journal of Education, Sports and Health, 2019)
A good effort for the further development of the men's handball is the analysis of the data of the last five world handball championships from 2009 to 2017. In recent years, the sport of handball has evolved in many levels, following the example of the evolution of most sports. Most changes are observed both in the defense and offensive levels, and the athletes' strength and explosion rate are remarkably improved. It is also important to note that the rapid development of the sport is mainly due to the European teams, which are more adapted to the modern handball. The first aim of this study was to conduct a technical analysis of modern handball characteristics and to determine factors related to the degree of improvement of the above characteristics in this sport. The second aim was to compare the data of the last five world championships in men's handball, considering which teams have won the world title most of the time. The main variables used to compare technical characteristics in the last five world men's handball championships were: the efficiency of attacks (Total Goals), the efficiency of 6m position throws (6m Goals), the efficiency of wing position throws (Wing Goals), the efficiency of 9m position throws (9m Goals), the efficiency of 7m position throws (7m Goals), the efficiency of fast breaks throws (Fast Breaks), the efficiency of break-through throws (Break-Through), the efficiency of assist throws (Assists) and the efficiency of steals (Steals). Data where used for analysis was taken by the International Handball Federation. ANOVA were used for finding differences between participant teams in the above characteristics. The results showed that the efficiency of all characteristics improved over the years in all teams.